16(2x-4)=4(8x+9)

Simple and best practice solution for 16(2x-4)=4(8x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16(2x-4)=4(8x+9) equation:


Simplifying
16(2x + -4) = 4(8x + 9)

Reorder the terms:
16(-4 + 2x) = 4(8x + 9)
(-4 * 16 + 2x * 16) = 4(8x + 9)
(-64 + 32x) = 4(8x + 9)

Reorder the terms:
-64 + 32x = 4(9 + 8x)
-64 + 32x = (9 * 4 + 8x * 4)
-64 + 32x = (36 + 32x)

Add '-32x' to each side of the equation.
-64 + 32x + -32x = 36 + 32x + -32x

Combine like terms: 32x + -32x = 0
-64 + 0 = 36 + 32x + -32x
-64 = 36 + 32x + -32x

Combine like terms: 32x + -32x = 0
-64 = 36 + 0
-64 = 36

Solving
-64 = 36

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6x+3+x=2+5x+5 | | 0.20t^2-45.0t+1000=0 | | 0.20t^2-45.0t=1000 | | 9+10s-4=9s+47-6s | | -16t^2+3t+1.3=0 | | -7(x+1)-13=26+3 | | -32+28=4 | | y/15+6=y/6+12 | | -9=-6+3x | | 16x^4=y^2 | | 0=2(3x-5)+8(4x+7) | | -16t^2+3t+1.3=h(t) | | 12+m/4=3d-1/2 | | (2x-3)(x+3)=3 | | 4(a+3)=6(a-(5-a)) | | 6(3+v)+36v=13v | | 7r-8r=6 | | 5xy-3y-4=0 | | X-3/5+3/5=-x/2 | | -5t-26=18t | | -(100/-4) | | 3x+9=15forx | | 0=16t^2+44t-24 | | -3/4+7/3 | | 4=2a+37 | | 4x^2=12x-8 | | -4x^2-40x-106=0 | | -17=1+4n-7n | | g(x)=2f(x) | | -4/3-1 | | 6y+4=3(2y-10) | | 4/3-1 |

Equations solver categories